Composition for crystallizing allulose
By controlling the content of impurities and particle growth in the production process of holographic crystal sweeteners, uniform particle size and high yield are achieved, solving the problem of insufficient crystal yield and particle size of holographic crystal sweeteners in the prior art, and improving production efficiency.
Patent Information
- Application Number
- JP2024207832
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-12-28
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-06
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, it is difficult for all ingredients to effectively improve the crystal yield and particle size of holographic crystal sweeteners, and there are problems of loss and purity during purification and crystallization.
By controlling the content and formation of impurities in the production process of holographic crystal sweeteners, especially the content of Impurity-S, adjusting the growth of crystal particles, achieving uniform particle size, and reducing losses in the recycling process, crystallization is performed using compositions of a specific concentration range.
The crystal yield and particle size uniformity of holographic crystal sweeteners are improved, the losses in the recycling process are reduced, and the production efficiency is improved.
Smart Images

Figure 2025019328000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a crystalline functional sweetener, and more particularly to a method for producing allulose crystals, which increases the crystal yield and particle size by controlling the content of impurities converted from allulose during the production of a crystalline functional sweetener, for example, allulose crystals. The present invention also relates to a composition for allulose crystallization, which has a uniform particle size and reduces losses during the recovery process, thereby improving the crystal yield, and has an allulose conversion product (Impurity-S) content adjusted to a specific concentration range. [Background technology]
[0002] General sugars, represented by sugar and starch sugar, form the largest market worldwide at about 65 trillion yen. However, as consumers worldwide are increasingly demanding health-conscious, functional and premium products, the market for functional sweeteners, including sugar alcohols such as xylitol, oligosaccharides such as fructooligosaccharides, functional sugars such as crystalline fructose, and sweeteners such as sucralose and aspartame, is growing.
[0003] Sweeteners are a general term for seasonings and food additives that give a sweet taste, and among the many sweeteners, sugar, glucose, fructose, etc. are the most widely distributed as natural ingredients in foods and are also the most widely used in the manufacture of processed foods. However, as negative aspects of sugar, such as its ability to cause tooth decay, obesity, and diabetes, have emerged, functional alternative sweeteners that can be used in place of sugar are attracting attention worldwide.
[0004] Recently, allulose has been in the limelight as a saccharide that can replace sugar or fructose as a functional sweetener. Allulose is produced by chemical or biological methods, but the allulose content in the product is low, so purification and concentration processes are required. However, concentrated syrups have limited application, so there is a high demand for crystalline powder, but allulose is difficult to crystallize due to its low crystallinity. In addition, even when allulose is produced by a biological method using allulose converting enzyme or a strain that produces the enzyme, the purity of D-allulose must be increased due to a low conversion rate before crystallization, so there are still unresolved issues regarding the purification process, purification yield, crystallization yield, etc., for the industrial use of D-allulose.
[0005] Therefore, there is an urgent need for a method for producing allulose crystals that can increase the crystal yield and particle size by minimizing the content of impurities contained in the allulose solution for crystallization or the generation of impurities during the allulose production process and controlling the content of impurities converted from allulose. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention relates to a method for producing allulose crystals to increase the crystal yield and particle size by controlling the content or production of impurities contained in a solution for producing the crystals.
[0007] In addition, the present invention provides a method for producing allulose crystals, which produces allulose crystals having a uniform particle size by appropriately controlling crystal particle growth, thereby reducing losses in the recovery process and improving the crystal yield, thereby increasing the productivity of the allulose crystallization process.
[0008] In addition, the present invention provides a composition for allulose crystallization, which has a uniform particle size and can reduce losses during the recovery process, thereby improving the crystal yield, and has an allulose conversion product (Impurity-S) content adjusted to a specific concentration range. [Means for solving the problem]
[0009] The present invention relates to a composition for allulose crystallization, which has a uniform particle size and reduces losses during the recovery process, thereby improving the crystal yield, and the content of allulose conversion product (Impurity-S) is adjusted to a specific concentration range, and a method for producing allulose crystals using the composition.The present invention also relates to a method for producing allulose crystals, which increases the crystal yield and increases the particle size by controlling the content or generation of impurities contained in the solution for producing the crystals.
[0010] Since allulose is unstable at lower pH and higher temperature (Figures 2 and 3), the content of allulose changes during the actual production process, especially during the concentration stage. This problem reduces the purity of high-purity allulose and has a significant impact on the crystallization stage. In fact, as the content of allulose decreases during this process, the content of the additionally produced allulose conversion product (Impurity) increases, and it has been confirmed in the present invention that this component has a significant impact on the crystallization of allulose. It has been found that when a component called Impurity-S is present among various allulose conversion products, it acts as an inhibitor for the growth of allulose crystal particles, and it has been discovered that this has a significant impact on the particle size and crystal yield of crystals.
[0011] Therefore, in the present invention, when performing the allulose crystallization process, impurities (Impurity-S) are adjusted to a specific content or less, for example, 2% by weight or less, before and after the concentration process after the high purity separation process, thereby preventing the size of allulose particles from becoming small, and allulose having a uniform particle size can be produced by appropriately controlling the growth of crystal particles. In addition, by growing the particles to a uniform size, losses in the recovery process can be reduced, and the crystal yield can be improved to increase productivity.
[0012] Allulose syrup, which is a raw material used in the allulose crystallization process, may contain various allulose conversion products, which are impurities other than allulose generated during the process of producing allulose, or allulose conversion products may be generated during the allulose crystallization process. By controlling a specific conversion product (hereinafter, Impurity-S) among the conversion products to a specific content or less, for example, 2 wt% or less, it is possible to improve the shape, structure and size of allulose crystal particles, crystal purity, crystal formation rate, and crystal yield. The Impurity-S acts as an inhibitor that prevents the growth of allulose crystal particles, thereby reducing the crystal yield. The present invention provides a method for increasing the allulose crystal particle size and improving the yield by controlling the allulose production process under conditions in which allulose conversion products are not generated.
[0013] The allulose conversion product (Impurity-S) has a mass / charge ratio measured by LC / MS analysis of 10-600 m / z, 10-550 m / z, 10-500 m / z, 10-450 m / z, 10-400 m / z, 20-600 m / z, 20-550 m / z, 20-500 m / z, 20-450 m / z, 20-400 m / z, 30-600 m / z, 30-550 m / z, 30-500 m / z, 30-400 m / z, 30-600 m / z, 30-550 m / z, 30-500 m / z, 30-400 m / z, 30-5 ...500 m / z, 30-500 m / z, 30-600 m / z, 30-550 m / z, 30-500 m / z, 30-400 m / z, 30-500 m / z, 30-500 m / z, 30-500 m / z, 30-500 m / z, 30-500 m / z, 30-500 m / z, 30-500 m / z The m / z range may be 50, 30-400, 40-600, 40-550, 40-500, 40-450, 40-400, 50-600, 50-550, 50-500, 50-450, or 50-400, or the m / z range may be a substance having a maximum peak measured at an elution time of 31±2 minutes when analyzed by HPLC analysis. The LC / MS analysis is for analyzing a substance obtained by separating a substance having a maximum peak measured at an elution time of 31±2 minutes when analyzed by HPLC analysis. .
[0014] In addition, the allulose conversion product (Impurity-S) may be an allulose modified product, an allulose modified polymer, or an intermediate substance produced and converted during the decomposition of allulose, and the molecular weight of the allulose conversion product (Impurity-S) may be, for example, 0.2 times or more, 0.3 times or more, 0.4 times or more, 0.5 times or more, 0.6 times or more, 0.7 times or more, 0.8 times or more, 0.9 times or more, 1 times or more, 1.1 times or more, 1.2 times or more, 1.3 times or more, 1.4 times or more, 1.5 times or more, 1.6 times or more, 1.7 times or more, 1.8 times or more, 1.9 times or more, or 2 times or more, and the upper limit may be 10 times or less, 9 times or less, 8 times or less, 7 times or less, 6 times or less, 5 times or less, 4 times or less, 3 times or less, 2 times or less, less than 1.5 times, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1 times or less, 0.9 times or less, 0.8 times or less, 0.7 times or less, 0.6 times or less, 0.5 times or less, 0.4 times or less, 0.3 times or less, or 0.2 times or less of the molecular weight of allulose, and the molecular weight of the allulose conversion product may have a molecular weight in a numerical range set by a combination of the lower limit and the upper limit, for example, The molecular weight of is 0.4 times or more to 10 times, 0.5 times or more to 10 times, 0.53 times or more to 10 times, 0.4 times or more to 9 times, 0.5 times or more to 9 times, 0.53 times or more to 9 times, 0.4 times or more to 8 times, 0.5 times or more to 8 times, 0.53 times or more to 8 times, 0.4 times or more to 7 times, 0.4 times or more to 6 times, 0.4 times or more to 5 times, 0.4 times or more to 4 times, 0.4 times or more to 3 times, 0.4 times or more to 2 times, 0.4 times or more to less than 1.5 times, 0.4 times or more to 1.5 times or less, 0.4 times or more to 1.4 times, 0.4 times or more to 1.3 times, 0.4 times or more to 1.2 times, 0.4 times or more to 1.1 times, 0. 4x or more to 1x, 0.4x or more to 0.9x, 0.4x or more to 0.8x, 0.4x or more to 0.7x, 0.4x or more to 0.6x, 0.4x or more to 0.5x, 0.5x or more to 7x, 0.53x or more to 7x, 0.4x or more to 6x, 0.5x or more to 6x, 0.5x or more to 5x, 0.5x or more to 4x, 0.5x or more to 3x, 0.5x or more to 2x, 0.5x or more to less than 1.5x, 0.5x or more to 1.5x or less, 0.5x or more to 1.4x, 0.5x or more to 1.3x, 0.5x or more to 1.2x, 0.5x or more to 1.1x, 0.5x or more to 1x, 0.5x or more to 0.9x, 0.The allulose modified product, allulose modified polymer, or intermediate substance produced and converted during the decomposition of allulose may have a molecular weight of 5 times or more to 0.8 times, 0.5 times or more to 0.7 times, 0.5 times or more to 0.6 times, 0.53 times or more to 6 times, 0.4 times or more to 5 times, 0.5 times or more to 5 times, 0.53 times or more to 5 times, 0.4 times or more to 4 times, 0.5 times or more to 4 times, 0.53 times or more to 4 times, 1.5 times or more to 10 times, 2 times or more to 10 times, 2 times or more to 4 times, or preferably 0.4 times or more to 4 times.
[0015] For example, the allulose conversion product (Impurity-S) may be converted into an allulose-modified polymer (tetramer analogue of allulose) having a molecular weight similar to that of a dimer as the allulose conversion product (Impurity-S) is continuously exposed to an external stimulus, such as high temperature or acidic conditions. This is because allulose is easily modified by an external stimulus, and random dehydration and condensation reactions with allulose or allulose conversion product are repeated to convert into the above-mentioned modified polymer. Alternatively, the allulose conversion product (Impurity-S) may be an intermediate substance generated and converted during the decomposition process of allulose.
[0016] Specifically, the component detected by LC-MS analysis with a molecular weight of 341 m / z is a component that increases the more severe the crystallization solution containing allulose is treated under harsh conditions, and molecular weight analysis confirms that allulose is a substance with a dimer-like structure that has been denatured by dehydration or condensation reactions. This is because the structure was inferred from LC-MS analysis and is C 12 H 22 O 11 It is predicted to be an allulose modified polymer with the chemical formula: 25 H 28 O 11 , C 24 H 42 O 21 Also is C 24 H 44 O 22 It was also confirmed that the content of allulose-modified polymers (tetramer analogs of allulose) having a molecular weight similar to that of the dimer of the allulose-modified polymer of 1. was increased. This can be seen as the fact that allulose is easily modified by external stress, such as heat treatment, and that it is converted into the above-mentioned substances by randomly repeating dehydration and condensation reactions with allulose or allulose conversion products.
[0017] Specifically, the components detected as contained in the allulose conversion product (Impurity-S) as a result of the LC-MS analysis may include intermediate substances (furan aldehyde intermediates) generated in the process of decomposing hexose such as allulose into HMF through a dehydration reaction, and Na + Ions are bonded Form [C6H 12 O6+Na] + , or Na in the allulose dimer molecule + The molecule with ions attached [CH 12 O6+Na] + may include.
[0018] In addition, the structure of the allulose conversion product was inferred by LC-MS analysis and found to have the molecular formula C x H y O z wherein x is an integer of 3 to 15, an integer of 3 to 14, an integer of 3 to 13, The y may be an integer from 3 to 12, an integer from 4 to 15, an integer from 4 to 14, an integer from 4 to 13, an integer from 4 to 12, an integer from 5 to 15, an integer from 5 to 14, an integer from 5 to 13, or an integer from 5 to 12; the y may be an integer from 1 to 15, an integer from 1 to 14, an integer from 1 to 13, an integer from 1 to 12, an integer from 2 to 15, an integer from 2 to 14, an integer from 2 to 13, an integer from 2 to 12, an integer from 3 to 15, an integer from 3 to 13, an integer from 3 to 12, an integer from 4 to 15, an integer from 4 to 14, an integer from 4 to 13, or an integer from 4 to 12; and the z may be an integer from 1 to 10, an integer from 1 to 9, an integer from 1 to 8, an integer from 1 to 7, or an integer from 1 to 6.
[0019] For example, allulose conversion products include C5H4O3, C5H6O4, C5H8O3, C5H4O2, and C5H 10 O3, C6H4O5, C6H 10 O3, C6H4O4, C6H6O3, C6H8O, C6H4O5, C6H6O4, C6H4O4, C6H4O3, C6H8O3, C 11 H8O6, C 12 H 12 O5, or C 12 H 10 May include substances with the chemical formula O5.
[0020] Specifically, allulose conversion products include levulinic acid (4-oxopentanoic), furfural, hydroxymethylfurfural (HMF), γ-hydroxyvaleric acid (GVB), 2,5-dimethylfuran, 2,5-furandicarboxylic acid (FDCA), 5-hydroxymethyl-2-furoic acid, and 2,5-formylfurancarboxylic acid. acid, 2,5-Furandicarbaldehyde, 2,5-bis-(hydroxymethyl)furan, bis(5-formyl-2-furfuryl) ether, 2-Furoic acid, 3-Furoic acid, 5-Hydroxyfurfural, 2,5-Dihydro-2,5-dimethoxyfuran, (2R)-5-Oxotetrahydro-2-furancarboxylic acid, 2,5-formylfuran carboxylic acid The furfuryl monomer may include one or more selected from the group consisting of 5,5'-methylenedi(2-furoic acid), 5,5'-Methylenedi(2-furoic acid), and bis(5-methyl furfuryl) ether.
[0021] According to the present invention, it is possible to carry out the production, separation and / or purification process of allulose under conditions where allulose conversion products are not produced, and to carry out a method for removing or reducing the content of conversion products (Impurity-S) contained in allulose syrup, which is the raw material used in the allulose crystallization process. Therefore, according to the method of the present invention, it is possible to reduce the content of impurities that hinder crystal growth by reducing the content of Impurities in the crystallization liquid, thereby improving the crystal shape and crystal yield.
[0022] Specifically, the content of the conversion product (Impurity-S) can be adjusted by preventing or reducing the production of Impurity-S, or by removing or reducing the generated Impurity-S. In one embodiment of the present invention, as a method for controlling the allulose production process under conditions for preventing or reducing the production of allulose conversion products, the allulose crystal grain size can be increased, the crystals can be formed into a shape close to a square shape, and the allulose yield can be improved. More specifically, when the content of the allulose conversion product (Impurity-S) component in the crystallization solution is controlled to be 2 wt% or less, the growth of allulose crystal grains and the yield can be improved.
[0023] The method for preventing or reducing the production of Impurity-S can be achieved by controlling the conditions of the allulose production process, such as the conditions under which allulose conversion products are not produced, particularly the conditions of the concentration process, such as controlling pH, temperature, and electrical conductivity. In addition, the method for removing or reducing the produced Impurity-S can be a method of treating with activated carbon or a method of redissolving the crystals obtained in the first crystallization and performing a second crystallization, and a method for removing impurities from allulose syrup can be used.
[0024] Specifically, the method for producing or adjusting the content of impurities may be carried out by one or more of the following methods.
[0025] As an example of a method for preventing or reducing the production of allulose conversion products (Impurity-S) in the allulose production process, the allulose production process may be carried out at a pH of 4 or higher and / or a temperature of 70° C. or lower. Specifically, allulose is relatively stable under conditions of a pH of 4 to 7 or pH 4 to 6 and a temperature of 70° C. or lower, preferably 60° C. or lower, and therefore, in allulose production processes such as decolorization, ion purification, and high-purity separation, the temperature of the reaction solution is controlled so as not to exceed 70° C., preferably 60° C., and in particular, it is preferable to control the concentration process in two or more stages to prevent continuous exposure to external stimuli.
[0026] In order to prevent or reduce the production of Impurity-S in the allulose production process, the concentration step can be performed at a temperature of 40 to 70°C or less on the allulose fraction obtained in the SMB chromatography separation step, and optionally the concentration step can be divided into at least two or more stages. For example, when the concentration step is performed in two stages, the first concentration step can be performed to obtain allulose syrup with a concentration of 30 to 50 Bx, and the first concentrate can be concentrated twice again with a concentration of 60 to 85 Bx. Preferably, an activated carbon treatment step can be additionally performed between the first and second concentration steps to remove Impurity-S contained in the concentrate or reduce its content.
[0027] As another example, a method for removing or reducing the content of conversion substances (Impurity-S) contained in allulose syrup, which is the raw material for allulose crystallization, is to treat it with activated carbon and adsorb and remove high molecular or low molecular weight organic substances, colored ionic substances, proteins, etc. that act as impurities or induce the denaturation of allulose.
[0028] In detail, the allulose reaction solution obtained from the substrate is subjected to SMB chromatography separation. Before concentrating the allulose fraction obtained by the above process, a process of treating with activated carbon can be performed to remove or reduce the content of conversion products (Impurity-S). The activated carbon process can be performed additionally by subjecting the allulose fraction obtained by the SMB chromatography separation process to an ion purification process.
[0029] The activated carbon process can be carried out by contacting the allulose solution with activated carbon, reacting at a temperature of 40 to 50° C. for 0.5 to 5 hours, and then subjecting the reaction solution containing the activated carbon to a solid-liquid separation process to obtain a filtrate and removing impurities as a filtration residue. The filtration can be carried out using a filtering device such as a filter press.
[0030] In the activated carbon reaction step, stirring can be selected, and the stirring speed of the reaction solution can be 5 to 500 rpm, preferably 50 to 300 rpm. The stirring speed can be appropriately selected in consideration of the degree of dispersion of the activated carbon and the cost required for stirring. The contact time between the activated carbon and the reaction solution can be appropriately selected in consideration of the degree of dispersion of the activated carbon and the efficiency of removing impurities, and can be, for example, 0.5 to 5 hours, preferably 0.5 to 2 hours. If the contact time is short, impurity removal, for example, decolorization, is not performed sufficiently, and if the contact time is long, destruction and browning of the main components occur.
[0031] The activated carbon used in the activated carbon treatment process may be derived from coal or wood, and impurities may be selectively removed depending on the pore size of the activated carbon.
[0032] As another example, a method for preventing or reducing the production of allulose conversion products (Impurity-S) in allulose crystallization compositions is to perform recrystallization. A first crystallization is performed with an allulose solution that has been subjected to a high-purity separation and concentration process, and the first crystallization stock solution is dehydrated and the recovered allulose crystals are dissolved in water again to prepare an allulose solution for crystallization, which is then introduced into a second crystallization process, thereby removing or reducing the content of allulose conversion products (Impurity-S) in the first crystallization process.
[0033] Therefore, one example of the present invention provides a method for adjusting the content of allulose conversion product (Impurity-S) contained in the allulose composition for crystallization to 2 wt% or less based on the solid content of the composition.
[0034] The method can be carried out by adjusting one or more conditions selected from the group consisting of the pH condition and the temperature condition of the composition, and the pH condition can be in the range of pH 4 to 7 and the temperature condition can be 70° C. or lower.
[0035] The allulose composition for crystallization can be produced by concentrating the allulose solution obtained by treating the allulose-containing reaction solution in an SMB chromatography separation step at a temperature condition of 40 to 70°C or less. The concentration step can be divided into at least two stages, and the first concentration is performed so that the allulose solution has a Bx concentration of 30 to 50, and the first concentrated solution is concentrated twice again to a Bx concentration of 60 to 85. An activated carbon treatment step can be additionally performed before the concentration step.
[0036] Another example of the present invention relates to a composition for crystallizing allulose, which contains an allulose conversion product (Impurity-S) content of 2 wt% or less, 1.9 wt% or less, 1.8 wt% or less, 1.7 wt% or less, 1.6 wt% or less, 1.5 wt% or less, 1.4 wt% or less, 1.3 wt% or less, 1.2 wt% or less, 1.1 wt% or less, 1.0 wt% or less, 0.9 wt% or less, 0.8 wt% or less, 0.7 wt% or less, 0.65 wt% or less, 0.6 wt% or less, 0.5 wt% or less, 0.4 wt% or less, 0.3 wt% or less, 0.2 wt% or less, 0.1 wt% or less, preferably 1.0 wt% or less, based on the total solid content of the composition (100 wt%). It is more preferable that the catalyst is free of impurities.
[0037] Preferably, the composition for allulose crystallization may contain an allulose content of 90 wt% or more, 91 wt% or more, 92 wt% or more, 93 wt% or more, 94 wt% or more, or 95 wt% or more, based on the total solid content of the composition being 100 wt%.
[0038] The viscosity of the allulose composition for crystallization may be 2 cps to 200 cps at a composition temperature of 45°C, and the electrical conductivity may be 1,000uS / cm or less, for example, 0.01 to 1,000uS / cm, preferably 30uS / cm or less, for example, 0.1 to 30uS / cm. The lower the electrical conductivity of the allulose crystallization composition, the more favorable it is for crystallization. The electrical conductivity of the allulose syrup is a value measured based on a solid content of 30Bx.
[0039] The allulose solution for crystallization may have a solid content of 60 to 85 Brix, for example, greater than 60 Brix to 80 Brix, 65 to 85 Brix, 65 to 80 Brix, or 68 to 85 Brix.
[0040] One example of the present invention relates to a method for producing allulose crystals using an allulose solution for crystallization, more specifically, the method includes the steps of providing a composition for allulose crystallization containing an allulose conversion product (Impurity-S) content of 2 wt% or less, 1.9 wt% or less, 1.8 wt% or less, 1.7 wt% or less, 1.6 wt% or less, 1.5 wt% or less, 1.4 wt% or less, 1.3 wt% or less, 1.2 wt% or less, 1.1 wt% or less, 1.0 wt% or less, 0.9 wt% or less, 0.8 wt% or less, 0.7 wt% or less, 0.65 wt% or less, 0.6 wt% or less, 0.5 wt% or less, 0.4 wt% or less, 0.3 wt% or less, 0.2 wt% or less, 0.1 wt% or less, preferably 1.0 wt% or less, based on the total solid content of the composition (100 wt%), and cooling the allulose aqueous solution to produce allulose crystals.
[0041] In one embodiment of the present invention, a method for producing allulose crystals includes a step of subjecting the allulose fraction obtained in the SMB chromatography separation step to secondary ion purification, a step of concentrating the ion-purified allulose fraction, and a step of crystallizing allulose from the concentrate to obtain allulose crystals and allulose crystallization mother liquor, and may optionally further include a step of recovering, washing, and drying the allulose crystals.
[0042] In addition, the allulose fraction itself obtained in the SMB chromatography separation process, or the solution obtained by ion-purifying the allulose fraction, can be treated with activated carbon before the concentration step to reduce or remove the content of allulose conversion product (Impurity-S).In addition, the allulose solution for crystallization can be concentrated, and then the first crystallization is performed, and the obtained crystals are dissolved and crystallized a second time to reduce or remove the content of allulose conversion product (Impurity-S).
[0043] In one embodiment of the present invention, the method for preparing the allulose composition for crystallization may include a step of subjecting the allulose fraction obtained by treating the allulose-containing reaction solution prepared from the substrate in an SMB chromatography separation process to secondary ion purification, and a step of concentrating the ion-purified allulose fraction, or may include an ion purification step for treating the allulose fraction obtained by treating in the SMB chromatography separation process, an activated carbon treatment step, or both the activated carbon treatment step and the ion purification step.
[0044] The step of providing an allulose composition for crystallization includes adjusting the content of an allulose conversion product (Impurity-S) to 2 wt% or less, 1.9 wt% or less, 1.8 wt% or less, 1.7 wt% or less, or 1.6 wt% or less based on the total solid content of the composition for crystallization (100 wt%). The present invention relates to a method for producing allulose crystals so as to contain 1.5% by weight or less, 1.4% by weight or less, 1.3% by weight or less, 1.2% by weight or less, 1.1% by weight or less, 1.0% by weight or less, 0.9% by weight or less, 0.8% by weight or less, 0.7% by weight or less, 0.65% by weight or less, 0.6% by weight or less, 0.5% by weight or less, 0.4% by weight or less, 0.3% by weight or less, 0.2% by weight or less, 0.1% by weight or less, preferably 1.0% by weight or less or preferably no allulose conversion product (Impurity-S).
[0045] The method for producing allulose crystals according to the present invention can result in an allulose crystal yield of 45% or more, preferably 48% or more, 50% or more, 53% or more, 54% or more, and more preferably 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, or 60% or more.
[0046] The content of the allulose conversion product can be adjusted by adjusting one or more selected from the group consisting of pH conditions and the temperature of the allulose solution, and the pH adjustment can be achieved in the range of pH 4 to 7, pH 4.5 to 7, or pH 5 to 7, preferably pH 5 to 7, and the temperature of the solution can be adjusted to 80°C or less, 75°C or less, 70°C or less, preferably 30 to 70°C or less, in the range of 30 to 69°C, 30 to 65°C, or 30 to 60°C.
[0047] Since allulose is unstable at low pH and high temperature, the content of allulose changes during the actual production process, especially during the concentration stage. This problem reduces the purity of allulose in the allulose solution, significantly affecting the crystallization stage. In the above process, the content of allulose decreases and the content of a specific allulose conversion product (Impurity) that is additionally produced increases, and it was confirmed that this component has a significant impact on the crystallization of allulose. It was found that when the content of a component called Impurity-S exceeds 2% among various allulose conversion products, it acts as a major obstruction factor for the growth of allulose crystal particles, and therefore it was confirmed that it has a significant impact on the particle size and crystal yield of crystals.
[0048] Specifically, as shown in Figures 1 and 2, the higher the storage temperature, the lower the allulose content and the higher the content of the allulose conversion product (Impurity-S). As shown in Figures 3 and 4, at 70°C and lowering the pH, the lower the allulose content and the higher the amount of allulose conversion product produced.
[0049] The allulose composition for crystallization according to the present invention may be a reactant containing allulose obtained by a biological or chemical process, an allulose fraction obtained by separating the reactant by SSMB chromatography, or a concentrate obtained by concentrating the allulose fraction. Prior to the concentration step for producing the allulose concentrate, an ion purification and / or activated carbon treatment step may be additionally performed, and the concentration step may be divided into at least two steps. The reactant containing allulose may be obtained from a fructose substrate by a biological or chemical method, and may preferably be produced by using an allulose converting enzyme or a microorganism that produces the enzyme by a biological method.
[0050] The allulose reaction solution may be subjected to a psicose conversion reaction product separation process, including an ion purification and simulated moving bed (SMB) chromatography separation process. In a specific example, the psicose conversion reaction product is subjected to an ion purification and SMB chromatography separation process to separate it into a psicose fraction having a higher psicose content than the conversion reaction product and a fructose raffinate, and the psicose fraction is subjected to a psicose concentration process and then to a crystallization process.
[0051] In order to obtain allulose crystals, the allulose content in the allulose solution must be contained at a high concentration in a supersaturated state, but since the allulose content of the allulose conversion reactant is low, direct crystallization cannot be performed; therefore, a process must be carried out to purify and concentrate allulose to the desired level before the crystallization step in order to increase the content.
[0052] In the method for obtaining the composition, the concentration process may be performed at a temperature of 90°C or less, 85°C or less, 80°C or less, 75°C or less, 70°C or less, for example, 40°C or more, 70°C or less, and specifically, may be performed using a thin film concentrator or a multiple effect evaporator. In one embodiment of the present invention, the step of concentrating the purified allulose solution may be performed at a temperature condition of 40 to 70°C or less. If the temperature of the concentrate exceeds 70°C, thermal denaturation of D-allulose may occur, and therefore the allulose conversion product (Impurity-S) according to the present invention may be generated or increased. In addition, since the temperature of the reactants increases rapidly due to the heat of evaporation when the concentration is performed, the temperature of the concentrate must be maintained at 70°C or less to perform the concentration quickly.
[0053] Specifically, the concentration step of the allulose fraction obtained in the SMB chromatography separation step can be carried out in various ways, so that the solid content of the concentrate can be 70 Brix or more. For example, the allulose fraction obtained by the simulated moving bed adsorption separation method (e.g., solid content of 20 to 30% by weight) can be concentrated to a solid content of 60 Brix or more by the concentration step. The composition for allulose crystallization according to the present invention can have a solid content of 60 or more and 85 Brix or less (Bx), for example, more than 60 Brix to 85 Brix, 65 to 85 Brix, 70 to 85 Brix, 75 to 85 Brix, more than 60 Brix to 83.5 Brix, 65 to 83.5 Brix, 70 to 83.5 Brix, or 75 to 83.5 Brix.
[0054] For example, the composition for crystallization may be an allulose fraction obtained by performing a simulated moving bed (SMB) chromatography separation process using a column chromatograph filled with a cation exchange resin having calcium active groups attached thereto, and more specifically, an allulose fraction obtained by performing activated carbon treatment, ion purification, and simulated moving bed (SMB) chromatography separation process on the allulose conversion reactant obtained by converting a fructose-containing raw material into allulose using a biological catalyst. The allulose fraction may be the one obtained by the SMB chromatography separation process itself or the one obtained by the ion purification process. The fructose content of the fructose-containing raw material may be 85% by weight or more based on the total solid content of the fructose-containing raw material (100% by weight), and the allulose conversion rate of the allulose conversion reaction may be 15% to 70% using a biological catalyst.
[0055] The allulose fraction obtained in the SMB chromatography separation step may be subjected to an additional ionic purification and / or activated carbon treatment step before being subjected to a concentration step.
[0056] In the method for producing allulose crystals according to the present invention, the temperature and concentration of the allulose concentrate solution can be adjusted to crystallize, and the supersaturated state required for crystallization can be maintained by lowering the temperature of the allulose solution or by changing the concentration of D-allulose in the D-allulose solution. In one embodiment of the present invention, the crystallization process can be monitored by collecting samples at regular intervals during the crystallization step and observing them with the naked eye or a microscope, or by analyzing the sugar concentration in the supernatant obtained by centrifuging the samples, and the temperature or the concentration of D-allulose can be adjusted according to the results. When the allulose concentrate solution is cooled to crystallize in order to produce allulose crystals, it can be rapidly cooled to a temperature range of 10 to 25°C using a heat exchanger, and then repeatedly heated and cooled to induce crystal growth.
[0057] In the method for producing allulose crystals according to the present invention, the temperature and concentration of the allulose concentrate solution can be adjusted to crystallize the allulose. Specifically, the supersaturated state required for crystallization can be achieved by lowering the temperature of the allulose solution or the concentration of D-allulose in the D-allulose solution. The allulose crystallization method according to the present invention can be carried out in various ways, preferably by a cooling method. In one example of the cooling method according to the present invention, the allulose solution is cooled at a temperature of 35 to 10°C to induce a supersaturated state and generate crystals. It is preferable to maintain the cooling rate at 0.01 to 20°C / min. If the cooling rate is low, the co-crystal formation time is long, resulting in low productivity, and if the cooling rate is high, crystals with small particle size are formed, making it difficult to recover the crystals.
[0058] The method for producing allulose crystals may include a step of generating crystal nuclei in an allulose solution containing 90% by weight or more of allulose and having an electrical conductivity of 60 to 85 Brix and 1,000 uS / cm or less, and a step of growing crystals by cooling the temperature of the solution.
[0059] Specifically, the method for producing allulose crystals may include a step of slowly stirring an allulose solution containing 90% or more by weight of allulose and having a Brix of 60 to 85 at a temperature of 20 to 40°C or 30 to 40°C, for example 35°C, to generate crystal nuclei, and a step of cooling the temperature of the solution to 10°C to grow crystals. The method may additionally include one or more steps of increasing the temperature of the solution to a range of 30 to 35°C and redissolving the fine crystals generated during cooling. The method for producing allulose crystals may additionally include a step of adding the seed crystals. The seed crystal addition step and the redissolution step may be selectively included in the method for producing allulose crystals, or both of the two steps may be included.
[0060] Generally, it is known that the larger the size of allulose crystals, the better the physical properties and the more convenient their use. In order to produce such large crystals, a seed crystal separated into a transfer process and a main crystallization process must all be carried out. However, the crystallization process according to the present invention can easily produce relatively large crystals in a high yield even in a single-step process.
[0061] In addition, the crystallization step may include a step of dissolving the fine crystals generated during cooling in the crystal growth step by increasing the temperature of the solution to 30 to 35° C. In the crystallization step according to the present invention, the crystal growth step and the fine crystal dissolving step may be repeated at least once.
[0062] In the process of producing the crystals, seeds may be added to increase the crystal growth rate and size.
[0063] In one specific example according to the present invention, allulose crystals are produced by slowly stirring an allulose solution containing 90% or more by weight of allulose based on the solid content and having a total solid content of 60 to 85 Brix at a temperature of 35°C to generate a small amount of crystal nuclei, and then cooling the solution to a temperature of 10°C by decreasing the temperature by 1°C per hour to grow crystals. Optionally, in order to re-dissolve fine crystals generated during cooling, the temperature of the solution is increased to 30 to 35°C to dissolve the fine crystals, and this process is repeated at least once to produce allulose crystals.
[0064] The method for producing allulose crystals according to the present invention may further include recovering the allulose crystals obtained in the crystallization process by various solid-liquid separation methods, for example, centrifugation, washing with deionized water, and drying. The drying process is carried out in a fluidized bed dryer or a vacuum dryer, but is not limited thereto.
[0065] Allulose crystals can be produced by the method of cooling the allulose composition for crystallization according to the present invention. The allulose composition for crystallization is as described above.
[0066] The allulose contained in the allulose crystals is 9% based on the total solid content of 100% by weight. It may be 4% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more by weight.
[0067] In the present invention, "purity of crystal" refers to the purity of allulose crystal. The physical properties including the purity of the crystal of the present invention can be determined by, for example, X-ray powder diffraction analysis, differential scanning calorimetry (DSC) analysis, infrared spectroscopy (FTIR) analysis, HPLC analysis, LC / MS analysis, etc., and the purity can be specifically analyzed by HPLC chromatography.
[0068] The allulose crystal according to one embodiment of the present invention may be an allulose crystal having an X-ray spectroscopy spectrum with peaks at diffraction angles (2θ) of 15.24, 18.78, and 30.84 ± 0.2°. In one embodiment of the present invention, the X-ray spectroscopy spectrum may be an allulose crystal having an X-ray spectroscopy spectrum with peaks at diffraction angles (2θ) of 15.24, 18.78, 30.84, and 28.37 ± 0.2°, at diffraction angles (2θ) of 15.24, 18.78, 30.84, and 31.87 ± 0.2°, or at diffraction angles (2θ) of 15.24, 18.78, 30.84, and 47.06 ± 0.2°. The diffraction angles having peaks in the X-ray spectrum of the allulose crystals are shown by selecting the main peaks and form-specific peaks in the upper (relative intensity%) ranges from the results of X-ray diffraction analysis.
[0069] The allulose crystals according to the present invention can be obtained by various crystallization methods, but the properties measured can be those of allulose crystals produced by the cooling method.
[0070] According to an embodiment of the present invention, the allulose crystals may have a Tm temperature of 125.8°C ± 5°C or a melting enthalpy (ΔH) of 200 to 220 J / g by DSC analysis, and the Tm may be 125.8°C ± 3°C. Differential scanning calorimetry (DSC) is operated by a temperature gradient and measures the energy provided to maintain the temperature rise of the allulose powder sample. In the DSC analysis of crystals, the higher the heat capacity, the less easily they melt, and the higher the heat capacity and the narrower the width of the endothermic peak, the more uniform and solid the crystals are formed.
[0071] Another example of the present invention is an allulose crystal produced by the composition for crystallizing allulose, which may preferably have one or more characteristics selected from the group consisting of the following (1) to (5): (1) Having a powder X-ray spectroscopy spectrum with peaks at diffraction angles (2θ) of 15.24, 18.78, and 30.84 ± 0.2°; (2) having a Tm temperature of 125.8°C ± 5°C by differential scanning calorimetry (DSC); (3) having a melting enthalpy (△H) of 200 to 220 J / g as determined by differential scanning calorimetry; (4) having an average major diameter of 350 μm or more, preferably 350 to 2,000 μm; and (5) The ratio of the major diameter length (micrometers) to the minor diameter of the allulose crystals (= major diameter / minor diameter) is in the range of 1.0 to 8.0.
[0072] The allulose crystal according to the present invention may have an average short diameter of 50 to 1,000 μm, preferably 50 to 500 μm, and an average long diameter of 350 μm or more, preferably 350 to 2,000 μm, and more preferably 400 to 2,000 μm.
[0073] In addition, the ratio (micrometer) of the major diameter to the minor diameter of the allulose crystals according to the present invention (=major diameter / minor diameter) is 1.0 to 8.0, 1.0 to 6.9, 1.0 to 6.0, 1. It can be 0-5.5, 1.0-5.0, 1.1-8.0, 1.1-6.9, 1.1-6.0, 1.1-5.5, 1.1-5.0, 1.3-8.0, 1.3-6.9, 1.3-6.0, 1.3-5.5, 1.3-5.0, 1.5-8.0, 1.1-6.9, 1.5-6.0, 1.5-5.5, 1.5-5.0, 2.0-8.0, 2.0-6.9, 2.0-6.0, 2.0-5.5, 2.0-5.0.
[0074] According to the powder XRD pattern analysis result of the allulose crystal according to the present invention, the allulose crystal according to the present invention has a rectangular hexahedron or a structure close thereto as a pure crystal particle. The closer the crystal structure of the present invention is to a cubic system, the higher the uniformity and firmness of the crystal is, which is more preferable.
[0075] In addition, the more uniform the crystals produced in the allulose crystallization process, the stronger the crystals are and the more uniform the particle size distribution is as a result of minimizing particle breakage, which improves flowability. On the other hand, if the degree of uniformity is low, the crystal particles break during the drying and transport stages, causing them to become undifferentiated and dissolve relatively easily, adversely affecting product quality.
[0076] The allulose crystal of the present invention has good flowability compared to fine powder, is less likely to caking, is stable during storage, and is easy to distribute and handle.In addition, the allulose powder has lower calories than sugar and has sweetness similar to that of sugar, so it can be easily and advantageously manufactured into mixed sweeteners, solid mixed sweeteners, chocolate, chewing gum, instant juice, instant soup, granules, refinement, etc.In addition, the allulose crystal powder can be used by being contained in various compositions such as food and beverages, luxury items, feed, cosmetics, and medicines. Effect of the Invention
[0077] The method for producing allulose crystals according to the present invention can prevent the size of allulose particles from becoming small by controlling the content of allulose conversion product (Impurity-S) contained in the solution for producing crystals, and can produce allulose with a uniform particle size by appropriately controlling the growth of crystal particles. In addition, by growing the particles to a uniform size, the loss in the recovery process can be reduced, and the crystal yield can be improved to increase productivity. [Brief description of the drawings]
[0078] [Figure 1] This is a graph showing the change in allulose content when allulose syrup with a pH of 5 and a Brix concentration of 70 is stored at different temperatures. [Diagram 2] This is a graph showing the change in the content of allulose conversion products when allulose syrup with a pH of 5 and a Brix concentration of 70 is stored at different temperatures. [Diagram 3] This is a graph showing the change in allulose content when allulose syrups having different pH and 70 Brix concentration are stored at 70°C. [Figure 4] This is a graph showing the change in the content of allulose conversion products when allulose syrups having different pH and a Brix concentration of 70 are stored at a temperature of 70°C. [Diagram 5] This is an optical microscope photograph of the allulose powder obtained in Example 5, measured at a magnification of X100. [Figure 6] 1 is a scanning electron microscope (SEM) photograph of the allulose powder obtained in Example 5, measured at a magnification of X50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0079] The present invention will be described in more detail with reference to the following examples, but the following examples are merely preferred examples of the present invention and are not intended to limit the present invention. EXAMPLES
[0080] Example 1: Production of allulose crystals Allulose syrup was produced from a fructose substrate using a biological method substantially the same as that described in Korean Patent Publication No. 2014-0054997. In order to remove impurities such as colored substances and ionic components, the allulose syrup was desalted by passing it through a room temperature column filled with a cation exchange resin, an anion exchange resin, and a resin containing a mixture of cation and anion exchange resin at a rate of twice the volume of the ion exchange resin per hour (1 to 2 times), and then separated and obtained as a high-purity allulose solution using a chromatography filled with a calcium (Ca2+) type ion exchange resin. The high-purity allulose syrup containing 97% by weight of allulose was concentrated to a concentration of 35Bx (w / w%) by the first concentration using the high-purity separation process (SMB), and was then concentrated again to produce allulose syrup for crystallization containing 97% by weight of allulose, with a concentration of 81Bx (w / w%) and an electrical conductivity of 12uS / cm. The electrical conductivity of the allulose syrup was measured based on a solid content of 30Bx. The concentrated allulose syrup was gradually cooled from a temperature of 35°C at which it was in a supersaturated state to a temperature of 10°C to grow crystals. In this case, allulose seed crystals were added and slowly stirred at a temperature of 35°C to generate a small amount of crystal nuclei, and then the temperature was reduced by 1°C per hour to grow crystals. In order to redissolve the fine crystals generated during the cooling process in the crystal growth process, the temperature of the solution was increased to 30-35°C to dissolve the fine crystals. The crystal growth process and the fine crystal dissolution process were repeated at least once to perform crystallization. The allulose crystals produced here were centrifuged to remove the mother liquor, washed with cooling water, and then dried and collected.
[0081] The allulose content of the crystallization solution, the content of the allulose conversion product (Impurity-S), and the purity of the allulose crystals were analyzed by HPLC under the following analysis conditions. Analytical column: Biolad Aminex HPX-87C column Mobile phase: water Flow rate: 0.6ml / min Column temperature: 80℃ Detector: RI detector
[0082] As a result of the HLPC analysis, based on the solid content of the allulose aqueous solution for crystallization being 100 wt%, the content of allulose conversion product (Impurity S) in the allulose aqueous solution for crystallization was 0.4 wt%, and the allulose content was 97.0 wt%. The yield of allulose crystals produced by the above method was 63.6%. The crystallization water rate is the weight of the allulose crystal powder recovered after dehydration and washing relative to the solid weight of the raw material allulose syrup for crystallization, expressed as a percentage.
[0083] Examples 2 and 3: Production of allulose crystals A method substantially similar to that of producing allulose in Example 1 was carried out, and by using a high-purity separation process (SMB), high-purity allulose syrup containing 96.6 wt% allulose was obtained at a concentration of 35Bx (w / w%) in Example 2, high-purity allulose syrup containing 95.8 wt% allulose was concentrated to a concentration of 35Bx (w / w%) in Example 3, and high-purity allulose syrup containing 95.5 wt% allulose was concentrated to a concentration of 35Bx (w / w%) in Example 6. The allulose solution was concentrated to prepare an allulose syrup having an 81Bx (w / w%) concentration for crystallization containing 96.6% allulose by weight and an electrical conductivity of 14 uS / cm in Example 2, an allulose syrup having an 81Bx (w / w%) concentration for crystallization containing 95.8% allulose by weight and an electrical conductivity of 14 uS / cm in Example 3, and an allulose syrup having an 81Bx (w / w%) concentration for crystallization containing 95.5% allulose by weight in Example 6. An allulose syrup for crystallization having a concentration of x (w / w%) and an electrical conductivity of 12 uS / cm was prepared. The electrical conductivity of the allulose syrup was measured based on a solid content of 30Bx. The concentrated allulose syrup was used for crystallization in the same manner as in Example 1, and the crystals were washed with cooling water, dried and collected. The allulose content of the crystallization solution, the content of the allulose conversion product (Impurity-S), and the purity of the allulose crystals were analyzed by HPLC using the same method as in Example 1. The results are shown in Table 1 below. Specifically, the yield of allulose crystals produced from the allulose syrup for crystallization in Example 2 (allulose conversion product content 0.3 wt%, allulose content 96.6 wt%) was 61.9%, the yield of allulose crystals produced from the allulose syrup for crystallization in Example 3 (allulose conversion product content 0.5 wt%, allulose content 95.8 wt%) was 61.6%, and the yield of allulose crystals produced from the allulose syrup for crystallization in Example 6 (allulose conversion product content 0.25 wt%, allulose content 95.5 wt%) was 62.1%.
[0084] Example 4: Production of allulose crystals A method substantially similar to that used for producing allulose in Example 1 was carried out, and a high-purity allulose syrup containing 97.0% by weight of allulose was obtained at a concentration of 35Bx (w / w%) by a high-purity separation process (SMB). In order to minimize impurities contained in the allulose syrup, it was treated with activated carbon suitable for impurity removal at a temperature of 40°C for 30 minutes and then filtered. The allulose syrup after the activated carbon treatment was concentrated to a concentration of 81Bx (w / w%) to prepare allulose syrup for crystallization having an electric conductivity of 10uS / cm and a concentration of 81Bx (w / w%) containing 97.3% by weight of allulose. The concentrated allulose syrup was gradually cooled from a temperature of 35°C at which it was in a supersaturated state to a temperature of 10°C to grow crystals. In this case, allulose seed crystals were added and slowly stirred at a temperature of 35°C to generate a small amount of crystal nuclei, and then the temperature was decreased by 1°C per hour to grow crystals. In order to redissolve the fine crystals generated during the cooling process in the crystal growth process, the temperature of the solution was increased to 30-35°C to dissolve the fine crystals. The crystal growth process and the fine crystal dissolution process were repeated at least once to perform crystallization. The allulose crystals produced here were centrifuged to remove the mother liquor, and the crystals were washed with cooling water, dried, and collected.
[0085] Example 5: Production of allulose crystals A method substantially similar to that of producing allulose in Example 1 was carried out, and high-purity allulose syrup containing 97.0% by weight of allulose was concentrated by a high-purity separation process (SMB) to obtain a concentration of 35Bx (w / w%). The allulose syrup was concentrated to a concentration of 81Bx (w / w%) to obtain high-purity allulose syrup containing 97% by weight of allulose based on a solid content of 100% by weight, thereby producing allulose syrup for crystallization having an electrical conductivity of 8uS / cm. Crystallization was performed using the concentrated allulose syrup using the same crystallization method as in Example 1, and the crystals were washed with cooling water, dried and collected. The obtained primary crystals were dissolved in water to prepare an allulose solution 81.2Bx. The allulose solution was analyzed by the HPLC analysis method of Example 1. As a result, the content of allulose conversion product (Impurity S) was 0.07 wt% and the allulose content was 99.5 wt%. The second crystallization process was carried out in substantially the same manner as the first crystallization process using the allulose solution prepared above as the raw material for the second crystallization process. The allulose crystals prepared here were centrifuged to remove the mother liquor, and the final crystals obtained in the second crystallization were washed with cooling water and dried. The secondary crystals were produced by recovering the crystals, and the yield of the secondary crystals was 62.5%.
[0086] [Table 1]
[0087] As shown in Table 1, the allulose crystal yield in Examples 1 to 3 exceeded 60%, whereas in Comparative Example 1, even if the allulose content of the crystallization solution was high, it was confirmed that proper crystals could not be obtained when the content of the allulose conversion product (Impurity-S) exceeded 2 wt%, and the crystal yield was significantly reduced due to small crystals.
[0088] Comparative Example 1: Preparation of allulose crystals when the allulose conversion content exceeds 2 wt% In order to investigate the allulose crystal yield when the allulose conversion product content of the crystallization solution exceeds 2 wt%, the crystallization solution for the secondary crystallization in Example 5 was subjected to acidic pH conditions or heat treatment conditions to induce the production of allulose conversion products. Specifically, the allulose crystals obtained by the first crystallization in Example 5 were dissolved in water to prepare a crystallization stock solution for the second crystallization, which was then heat-treated for 3 hours at pH 3.5 and 80°C to prepare a crystallization stock solution. Crystallization was performed using the concentrated allulose syrup in the same crystallization method as in Example 1, and the crystals were washed with cooling water, dried and collected. In the same manner as in Example 1, the content of allulose in the crystallization solution, the content of allulose conversion product (Impurity-S), and the purity of the allulose crystals were analyzed by HPLC as follows, and the results are shown in Table 2 below.
[0089] Comparative Example 2 and Examples 7-8: Production of allulose crystals depending on the content of allulose conversion product The crystallization stock solution for the secondary crystallization was prepared by dissolving the allulose crystals obtained by the primary crystallization in Example 5 in water, and was heat-treated at pH 4.5 and 70° C. for 6, 13, or 24 hours to prepare a crystallization stock solution. The contents of allulose and allulose conversion products contained in the crystallization stock solution are shown in Table 2 below. The method of crystallization using the prepared crystallization solution was substantially the same as that in Example 1. Specifically, in Comparative Example 2 and Examples 7 to 8, crystallization solutions having the allulose content and allulose conversion product content shown in Table 2 below were prepared using different heat treatment times, and an allulose crystallization process was carried out. The allulose content of the crystallization solution, the content of the allulose conversion product (Impurity-S), and the purity of the allulose crystals were analyzed by HPLC using the same method as in Example 1. The results are shown in Table 2 below.
[0090] [Table 2]
[0091] In the case of Comparative Example 2, the crystallization solution had a low purity of allulose and a high content of allulose conversion product, so the crystal particles did not grow well and were formed into fine crystals, which were very difficult to dehydrate and wash. In Comparative Example 1, as in Comparative Example 2, it was confirmed that the higher the content of allulose conversion product, the less the crystal particle size growth was and the more fine the crystals were formed. In the cases of Examples 7 and 8, it was confirmed that the content of allulose conversion product was less than 2 wt%, and a higher crystal yield was shown compared to the comparative examples.
[0092] Experimental Example 1: LC-MS analysis of allulose conversion product (Impurity S) (1) Analysis of allulose conversion product (Impurity S) of Example 2 In the HPLC analysis of the allulose syrup for crystallization used in Example 2, the impurity fraction separated from the peak at an elution time of 31±2 minutes was directly obtained, and the liquid diluted during the separation and fractionation was freeze-dried to concentrate at a concentration of about 100 times and used for analysis. The molecular weight of the impurities was analyzed using a liquid chromatography / mass spectrometry (LC / MS system, model name: LTQ, manufacturer: Thermo Finnigan, USA), and the molecular weight of the allulose conversion product (Impurity S) measured by the LC / MS analysis method was a substance with an m / z (ratio of mass / charge) range of 300 to 400.
[0093] (2) Analysis of allulose conversion products (Impurity S) of Comparative Example 2 and Examples 7-8 The heat-treated crystallization stock solution used in Comparative Example 2 and Examples 7 to 8 in the HPLC analysis was used for LC-MS analysis in a manner substantially similar to the LC-MS analysis method. LC-MS analysis was performed to examine the change in molecular weight of allulose and allulose conversion products due to the heat treatment, and the analysis results of the allulose content and allulose conversion product content (%) contained in the crystallization stock solution used in Comparative Example 2 and Examples 7 to 8 are shown in Table 3 below. Table 3 below shows the LC-MS analysis data for allulose syrups with different heat treatment times (Examples 7, 8, and Comparative Example 2), and the area values of the peaks detected for each molecular weight (m / z) are converted into percentages. In Row 1 of Table 3, the molecular weight of 179.1 m / z is allulose. In Table 3 below, Rows 4, 8, and 10 show that the content of allulose conversion product (Impurity S) increased after heat treatment, and the remaining rows show that the content of allulose conversion product (Impurity S) decreased after heat treatment.
[0094] [Table 3]
[0095] As shown in the analysis results, it was confirmed that the allulose content decreased and the impurity content increased as the heat treatment time increased, even in the molecular weight analysis. In Row 1 of Table 3, the molecular weight of 179.1 m / z is allulose, and it was confirmed that the peak area value decreased after heat treatment. On the other hand, the component detected at molecular weight 341 m / z (Row 5 of Table) is a component that increases as the crystallization stock solution containing allulose is heat treated, and it was confirmed by molecular weight analysis that it is a substance with a dimer-like structure in which allulose is modified by dehydration or condensation reaction. This was confirmed by the structure inferred by LC-MS analysis as C 12 H 22 O 11 It is predicted to be an allulose modified polymer with the chemical formula: 25 H 28 O 11 , C 24 H 42 O 21 or C 24 H 44 O 22It was also confirmed that the content of allulose-modified polymers (tetramer analogs of allulose) having a molecular weight similar to that of the dimer of the allulose-modified polymer of also increased. This can be seen as the fact that allulose is easily modified by external stimuli (stress), for example, acidic pH and / or heat treatment in Comparative Examples 1 and 2, and is converted into the above-mentioned substances by randomly repeating dehydration and condensation reactions with allulose or allulose conversion products.
[0096] (3) Analysis of the allulose conversion product of Example 3 In the HPLC analysis of the allulose syrup for crystallization used in Example 3, the impurity fraction separated from the peak at an elution time of 31±2 minutes was directly obtained, and the liquid diluted during the separation and fractionation was freeze-dried and concentrated to about 100 times the concentration for analysis. The molecular weight of the allulose conversion product was analyzed using a liquid chromatograph / mass spectrometer (LCMS). -Equipment product name: Ultimate-3000 ISQ EC (Thermo Fisher) -Analytical column: Bio-rad Aminex HPX-87C -Column temperature: 80℃ -Flow rate: 0.3mL / min -Solvent: distilled water -Injection volume: 5μl LC / MS analysis of the allulose conversion product showed peaks at 55.22 m / z, 60.24 m / z, 74.14 m / z, 79.25 m / z, 82.22 m / z, 83.23 m / z, 109 m / z, 117 m / z, 124.26 m / z, 127.1 m / z, 141.5 m / z, 144 m / z, 163.23 m / z, 203.16 m / z, and 365.16 m / z, with the main peaks being around 127 m / z, around 163 m / z, around 198.2 to 203 m / z, and around 365 m / z. Therefore, allulose conversion products are molecules composed of C, H, and O with carbon numbers of 5 to 12, and have a molecular weight charge value m / z of 50 to 400. They are modified substances derived from allulose, and contain HMF and levulinic acid components, and are derivative substances containing a furan structure. Specifically, the 163 m / z peak is thought to be an intermediate substance (furan aldehyde intermediate) generated in the process in which hexose such as allulose is decomposed by HMF through a dehydration reaction, and the 198.2 to 203 m / z peak is a form in which Na+ ions are bound to allulose molecules [C6H 12 O6+Na] + In the case of the 365 m / z peak, it is believed that the allulose dimer molecule contains Na + Ions bond [C6H 12 O6+Na] + was thought to be a molecule. Based on the LC / MS analysis results of the allulose conversion product, the compounds contained in the allulose conversion product are shown in Table 4 below.
[0097] [Table 4]
[0098] (4) LC / MS analysis of 5-HMF LC / MS analysis of 5-HMF confirmed that the allulose conversion product contained 5-HMF. As the 5-HMF analysis sample, a standard substance (SIGMA-ALDRICH, CAS Number 67-47-0) was purchased and used. As a result, the molecular weight m / z values of the structure that can be generated by charge transfer, elimination, and dehydration reactions of 5-HMF in an aqueous solution were shown, with peaks at 79.09 m / z, 109 m / z, 124.22 m / z, 127 m / z, 144.15 m / z, etc., and the LC / MS analysis results of the allulose conversion product partially matched the LC / MS analysis peaks, confirming that the allulose conversion product contains 5-HMF.
[0099] Experimental Example 2: Stability analysis of allulose In order to test the effect of temperature on allulose and allulose conversion water, 30g portions of allulose syrup containing 97% by weight of allulose in Example 1 were placed in constant temperature water baths at different temperatures, and samples were taken over time to analyze the changes in content. The results are shown in Figures 1 and 2. Figure 1 is a graph showing the change in allulose content when allulose syrup with a Brix concentration of 70% and a pH of 5 is stored at different temperatures. Figure 2 is a graph showing the change in the content of allulose conversion product when allulose syrup with a Brix concentration of 70% and a pH of 5 is stored at different temperatures. As shown in Figures 1 and 2, the higher the storage temperature, the lower the allulose content and the higher the content of the allulose conversion product (Impurity-S). In addition, to test the effect of pH on allulose and allulose conversion products, the syrup with 97.0% allulose content in Example 1 was adjusted to different pH values using caustic soda and hydrochloric acid solutions, and then stored at the same temperature (70°C) and sampled over time to analyze the changes in content. The results are shown in Figures 3 and 4. Fig. 3 is a graph showing the change in allulose content when allulose syrups with different pH and 70 Brix concentration are stored at 70°C. Fig. 4 shows the change in allulose conversion product when allulose syrups with different pH and 70 Brix concentration are stored at 70°C. 3 and 4, the lower the pH at 70° C., the lower the allulose content, and the higher the amount of allulose conversion product produced. Therefore, allulose is more unstable at lower pH and higher temperature, and the content of allulose changes during the actual production process, especially during the concentration stage. This problem reduces the purity of high-purity allulose and has a significant impact on the crystallization stage. In fact, during this process, the content of allulose decreases and the content of a specific allulose conversion product (Impurity) that is additionally produced increases, and it has been confirmed that this component has a significant impact on the crystallization of allulose. It has been found that when the content of a component called Impurity-S exceeds 2% among various allulose conversion products, it acts as a major obstruction factor for the growth of allulose crystal particles, and this has been confirmed to have a significant impact on the particle size and crystal yield of the crystals.
[0100] Experimental Example 3: Characterization of allulose crystals (1) Analysis of crystal size distribution The particle size distribution of the allulose crystals obtained in Example 5 was confirmed using standard mesh sieves of different mesh sizes. Standard mesh sieves with mesh sizes of 20, 30, 40, 60, 80, and 100 mesh were used, and the particle size distribution of the crystal particles was measured based on the hole size of the standard mesh sieve. The hole sizes of the standard mesh sieves for each mesh are 850, 600, 425, 250, 180, and 150 μm. 100 g of each sample was weighed, placed in a standard mesh sieve for each mesh size, and vibrated for 3 minutes to pass through the standard mesh sieve. The weight of the samples remaining on the sieve for each mesh size was measured and the percentage values are listed in Table 5. In Table 5 below, the particle size distribution for each mesh is shown as a numerical value in terms of the weight % of the particles.
[0101] [Table 5]
[0102] As shown in Table 5, the allulose crystals of Example 5 showed a very narrow particle distribution concentrated at 90.2 wt%, and the allulose crystals of Example 3 showed the most abundant distribution at 40↑, but were evenly distributed at 80↑, 60↑, 40↑, and 30↑, confirming that the particle distribution was widely spread. As in Example 5, it was confirmed that the smaller the major diameter / minor diameter ratio and the firmer the crystal particles, the lower the fine powder content of the product and the more uniform the particle size distribution. In addition, the larger the major diameter / minor diameter ratio and the lower the uniformity of the particles, the more undifferentiated the particles are during drying and transportation, resulting in a wide range of particle size distribution due to particle breakage.
[0103] (2) Crystal morphology and grain size analysis An optical microscope photograph of the allulose crystals obtained in Example 5 measured at a magnification of ×100 is shown in Figure 5. A scanning electron microscope (SEM) photograph of the allulose crystals obtained in Example 5 measured at a magnification of ×100 is shown in Figure 6. In addition, the major diameter (vertical) and minor diameter (horizontal) of the nine samples of allulose crystals obtained in Example 5 were measured, and the particle diameter ratio (= major diameter / minor diameter) was obtained and shown in the following Table 6. Specifically, the minor diameter length (μm) of five crystals was set to 1, and the major diameter length (μm) ratio was shown based on this.
[0104] [Table 6]
[0105] As shown in Figure 6, the allulose crystal according to the present invention has a rectangular hexahedron or a crystal structure close thereto. The minor diameter length (μm) of the crystal shown in Table 2 is set to 1, and the major diameter length (μm) ratio shown based on this is an average of 1.6 in the case of Example 5, where each crystal face grows uniformly to form an orthorhombic crystal form close to a square. It was also confirmed that the more uniformly the crystal faces grow, the smaller the major diameter / minor diameter ratio tends to be. This is interpreted as the lower the purity of allulose in the crystallization raw material, the more components other than allulose act as impurities that hinder the crystal growth of pure allulose, affecting the crystal shape.
[0106] (3) Differential scanning calorimetry (DSC) analysis DSC analysis was carried out on the allulose crystals obtained in Example 5. The specific DSC analysis conditions are as follows. Equipment name: DSC [differential scanning calorimetry] Manufacturer: Perkin Elmer Method: 30~250℃, 10℃ / min temperature increase, N2 gas purge (Reference method: ASTM D 3418) The DSC analysis results of the allulose crystals are shown in Table 7 below.
[0107] [Table 7]
[0108] As a result of the DSC analysis, the crystals of Example 5 were measured to have a high Tm value and a high heat capacity. In the DSC analysis of crystals, it can be predicted that the higher the heat capacity, the less easily the crystals melt, and the higher the heat capacity and the narrower the endothermic peak width, the more uniform and solid the crystals are formed. Considering the heat capacity and endothermic peak enthalpy value of Example 5, it was confirmed that the crystals of Example 5 were relatively more uniform and solidly formed.
[0109] (4) Infrared absorption (IR) spectrum analysis In order to confirm the prepared allulose crystals, infrared absorption (IR) spectrum analysis was performed on the crystals of Example 5 under the following measurement conditions. Analytical equipment: TENSOR II with Platinum ATR, Manufacturer: Bruker (German) Detector: highly sensitive photovoltaic MCT detector with liquid nitrogen cooling Scan count: 64 scans at 20 kHz Scan range: 800-4,000cm-1 and averaged at 4cm-1 resolution. According to the results of infrared absorption (IR) spectrum analysis, it was confirmed that the allulose molecular structure is composed of functional groups -OH, COC, CC, C-OH, etc., and has unique structural characteristics unique to allulose molecules. Therefore, it was confirmed that the crystals of Example 5 are the same allulose crystals.
[0110] (5) X-ray diffraction (XRD) analysis X-ray diffraction analysis was performed under specific analytical conditions for the allulose crystals obtained in Example 5, and the top five peaks (relative intensity%) and form-specific peaks from the results of the X-ray diffraction analysis of the allulose crystals obtained in Example 5 were selected and are shown in Table 8. Analytical equipment: D / MAX-2200 Ultima / PC Manufacturer: Rigaku International Corporation(Japan) X-ray sauce system target: sealed tube Cu Tube voltage: 45kV / Tube current: 200mA Scan range: 5~80° 2θ Step size: 0.019° Scan speed: 5° / min
[0111] [Table 8]
[0112] As shown in Table 8, the allulose crystals obtained in Example 5 were confirmed to have specific peaks in the powder X-ray spectroscopy spectrum with Angle 2-Theta degree values of 15.24, 18.78, and 30.84; 15.24, 18.78, 30.84, and 28.37; 15.24, 18.78, 30.84, and 31.87; 15.24, 18.78, 30.84, and 47.06; or 15.24, 18.78, 30.84, 28.37, 31.87, and 47.06.
Claims
[Claim 1] The invention described herein.
Citation Information
Patent Citations
Method for producing d-psicose crystal
JP2011206054A
Method for producing d-psicose crystals
JP2017532382A
Mixed sugar granular powder and method for preparing same
WO2016182235A1